Pengembangan Digital School System Dalam Menghadapi Era Society 5.0 Di Sekolah Indonesia Kuala Lumpur (SIKL): indonesia - Khusunul Inayah; Eva Yuli Nor Farika; Mustaghfiroh; Ahmida Nurronia; Elya Umi Hanik (JEID: Journal of Educational Integration and Development, 2021)
The development of technology has now spread to all aspects of life. One of them is in the field of education, namely the discovery of a digital school system. Digital School is an educational reform mechanism through the transformation of teacher practices and to actualize digital learning, transforming school capacity into an internet-based form so that real-life learning can be improved beyond the existing space and time. The purpose of this study was to determine the development of digital schools in the 5.0 era at the Kuala Lumpur Indonesian School (SIKL). This writing uses a qualitative descriptive method, namely presenting data in written form by analyzing according to the facts studied so as to be able to explain how the learning process of students at school. The results in this study can also find out the progress of information and communication technology (ICT). With the development of technology as a mechanism for educational reform through the transformation of teacher practices and to actualize digital learning, changing the capacity of schools towards a technology-based form, are Digital lesson plan program, SIKL Channel TV, and Digital Media Teacher, with this paper, it is hoped that readers can take lessons and be able to develop digital schools in the 5.0 era.